Edukasi Pemilahan dan Pengelolaan Sampah di RT 09 RW 02 Desa Mendalo Darat Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Mekarisce, Arnild Augina; Rodhiyah, Zuli; Samsidar, Samsidar; Lesmana S, Oka; Putra, Fernando Mersa (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Proper waste sorting and management are environmental health efforts that form an important part of the overall public health framework, as a healthy environment can prevent nearly a quarter of the global disease burden. Based on preliminary studies in Mendalo Darat Village, it was found that many people still dispose of waste in their yards and on the edges of ditches. There are also 20 illegal temporary waste storage sites (TPSS), especially in RT 09 RW 002, which is the largest and most extensive illegal TPSS location. This community service program aims to increase community understanding and awareness of waste sorting and management in RT 09 RW 002, Mendalo Darat Village, Jambi Luar Kota District. The program was conducted in the form of education on the importance of household-scale waste sorting and management, attended by 54 community members on October 12, 2024. Based on the pre-test results, the average score was 56% correct answers, which increased to 71% in the post-test. The test results revealed that the community still lacks understanding about organic and inorganic waste, as well as how to distinguish which types of waste can be recycled or composted. Additionally, the community reported difficulties in disposing of waste legally at the TPSS, as there are no legal TPSS containers in the village. In addition, waste collectors do not collect waste regularly every day, and in some cases only collect waste twice a week, whereas ideally waste should be transported to the TPSS within a maximum of 24 hours. It is hoped that the insight, knowledge, and awareness of the community will be further improved regarding the importance of waste sorting and management for all family members, regular waste collectors daily waste collection, and the establishment of a village-scale waste management center in the form of an Integrated Waste Processing Site (TPST) that is easily accessible to the community.